A comprehensive three-phase opiate sparing multimodal pain protocol for hip arthroscopy: a retrospective review. Issue 3 (11th December 2020) - Kolaczko, Jensen G; Knapik, Derrick M; Kroneberger, Elisabeth; Chadha, Amrita; Salata, Michael J
Abstract: The aim of this study is to assess the efficacy of a three-phase, multimodal, perioperative pain protocol for primary hip arthroscopy based on pain scores, narcotic use, time to discharge, hospital admission and complications. A retrospective study of patients undergoing primary hip arthroscopy over a 48-month time period was conducted. Patients were separated into a multimodal group consisting of non-narcotic medication, local analgesia and a peripheral nerve block (PNB) versus patients receiving only a PNB. Differences in post-anesthesia care unit (PACU) visual analog scores, PACU time to discharge, PACU opioid consumption, hospital admission and complications between protocols were recorded and analyzed. There were 422 patients who underwent 484 surgeries, with 15 patients crossing over pain protocol groups for surgery on the contralateral hip. One hundred and ninety-six patients underwent 213 procedures in the multimodal group and 241 patients underwent 271 procedures in the PNB group. No differences in baseline characteristics were appreciated between groups. Mean time to discharge was significantly shorter in the multimodal group (137.4 ± 49.3 min versus 176.3 ± 6.5 min; P  < 0.001) which also had less post-operative admissions (0 versus 9; P  = 0.006) than the PNB group. In patients who crossed over protocol groups, a statistically shorter time to discharge was appreciated with the multimodal protocol compared with the PNB protocol (119.9 ± 32.1 min versus 187.9 ± 9.2; P  = 0.012). The three-phase, multimodal pain protocol led to significantly faster discharge times and fewer hospital admissions when compared with isolated PNB in patients undergoing primary hip arthroscopy.